Preliminary design of carbon composite facing for dry clutch disc of mini agricultural tractor - Munir, F.A; M. Azmi, M.Irwan; M. Zin, Mohd Rody; Salim, M.A; Hassan, Muhammad Zahir (Praise Worthy Prize, 2011)
In this paper, the preliminary design of carbon composite clutch facing for the use of mini agricultural tractor dry clutch disc is presented. The main factor that needs to be considered in order to design a clutch disc facing is the torque produced by the engine. An optimum clutch facing disc should have minimum in weight, simple to manufacture and high reliability. Finite element analysis is conducted to determine the maximum stress the designed clutch disc facing before the fabrication take place. The design carbon facing is then fabricated by using Computer Numerical Controlled (CNC) 5-axis milling machine. The completed design will then used for experimental analysis to determine its reliability and durability.